The P600 as a correlate of ventral attention network reorientation. (May 2015) - Sassenhagen, Jona; Bornkessel-Schlesewsky, Ina
Abstract: When, during language processing, a reader or listener is confronted with a structurally deviant phrase, this typically elicits a late positive ERP deflection (P600). The P600 is often understood as a correlate of structural analysis. This assumption has informed a number of neurocognitive models of language. However, the P600 strongly resembles the P3, likely a more general electrophysiological correlate of reorientation behaviour supported by noradrenergic input to the ventral attention network/VAN. Some researchers have proposed that the P600 is an instance of the P3, not a distinct component reflecting the analysis of structured inputs. Here, we tested the P600-as-P3 hypothesis by estimating the alignment of the P600 elicited in a visual sentence processing task to simultaneously collected behavioural measures. A similar analysis was undertaken for a P3 elicited in a separate non-linguistic (face detection) task. Since the P3 is usually aligned to reaction time/RT, the same should hold for the P600; a failure to find RT alignment of the P600 would pose a problem for the P600-as-P3 hypothesis. In contrast, RT alignment of the P600 would associate it with the well-established VAN/Locus Coeruleus – Noradrenaline – Network subserving cortical reorientation. We failed to falsify the hypothesis of RT alignment. Secondary measures, while less unambiguous, were more in agreement with the P600-as-P3 hypothesis. We interpret our results as corroborating the hypothesis that the P600 is a P3, in that it shows that the P600 is RT-aligned. This perspective is unpredicted by an account of the P600 as indexing high-level processing.